Supplier’s selection of plate material using analytical hierarchy process and additive ratio assessment methods - Salsabila, Ja’iza; Ernawati, Dira (International Journal of Industrial Optimization, 2023)
PT PAL Indonesia (PERSERO) is among the prominent shipyard companies in Indonesia that currently employs a simplistic supplier selection weighting system, prioritizing low prices and material specification conformity. This approach often leads to subjective assessments, making it challenging for the company to identify suitable suppliers from a large pool. Therefore, this study proposed a methodology to enhance supplier selection by incorporating additional criteria based on Dickson’s criteria and company policies. The Analytical Hierarchy Process (AHP) and Additive Ratio Assessment (ARAS) methods were utilized for this purpose. The findings indicate that PT Krakatau Steel (A1) emerges as the top-ranked supplier with a Ki value of 0.19, followed by PT Diansakti Sejahtera (A5) in second place with a Ki value of 0.157, and PT Gunawan Dianjaya Steel (A3) in third place with a Ki value of 0.152. PT Jastindo Raya (A4) secures the fourth position with a Ki value of 0.151, while PT Gunung Raja Paksi (A2) takes the fifth and final spot with a Ki value of 0.15. This research helps the company effectively select the best suppliers, particularly in the procurement sector, by employing the AHP-ARAS method and considering Dickson’s criteria, thereby addressing existing gaps the company encounters.